Zastosowanie Stabelaryzowanych Funkcji do Obliczania Ugięć i Wielkości Statycznych w Ortotropowych Pasmach i Półpasmach Płytowych - A. Kacner; Z. Kaczkowski (Engineering Transactions)
A plate strip simply supported on the edges and a semi-strip simply supported on the infinite edges, one of the three fundamental boundary conditions (5.8), (5.9) or (5.10) being satisfied at the transverse edge, are considered. The material of the plate is orthotropic, the principal directions of elasticity coinciding with those of Cartesian coordinate axes (Fig. 1). Three types of load are considered: a concentrated force P and two concentrated moments Mx and My. The deflection surfaces and the mechanical quantities are expressed by simple trigonometric series, which can be represented for each of the three types of orthotropy by means of fifteen functions tabulated in Ref. [6].